Abandono e permanência escolar na educação profissional e tecnológica: olhares de trabalhadores da educação do Instituto Federal de Santa Catarina - Zanin, Alexsandra Joelma Dal Pizzol Coelho (2019)
School dropout and permanence are complex and multifaceted phenomena that involve socioeconomic, political and cultural issues. In Brazil, the recent expansion of the Federal Network of Professional and Technological Education, while contributing to the democratization of access to this type of education, has also led to the intensification of these phenomena, giving rise to concerns both about the necessary actions to ensure the permanence of students and to contain the growing dropout of studies. Seeking to dialogue on these issues, this paper aimed to analyze the view of the Professional and Technological Education workers of the Federal Institute of Santa Catarina (IFSC) on the factors that involve dropping out and permanence in subsequent technical courses of the technological axis Control and Industrial Processes. Supported by the assumptions of dialectical historical materialism, the established debate, however, presents authors from different perspectives and theoretical conceptions in search of deepening the theoretical and ideological clashes that permeate the discussions about school dropout and permanence. The approach to the phenomenon occurred through qualitative research, dialectical perspective and exploratory nature, using methodological approaches that involved bibliographic, documentary and field research, with semi-structured interviews with 36 education workers working in the rectory and six IFSC campuses located in different regions of the state of Santa Catarina. The results demonstrated the multiple and complex motivators of dropping out or permanence in Professional and Technological Education, as well as the different looks according to the positions and functions they occupy. In general, they signaled the absence of evaluations and follow-up of school permanence actions, as well as pointed to the few and fragmented institutional debates on this subject. It revealed the absence, both in local actions and in institutional policies to support permanence, of factors aiming at modifying the structural essence of Professional and Technological Education, thus not involving central issues for permanence or dropout, such as pedagogical practices, curriculum restructuring, needs of its subjects, school culture, public school management, continuing education of workers, among other issues. The research also emphasized that school dropout reflects an excluding structure, which strengthens a model of society based on capitalist principles, such as meritocracy, individualization, blaming subjects, market education and structural duality.